(untitled) (Palíndromo, 2025)
This article is dedicated to an analysis of the album Isto (2019), a work by Cildo Meireles performed with the voice of Íris Lettieri. Just as in Isto the artist used a loop to bring together, sonically and subtly, both sides of the record, the writing of this article is done in a loop, not structured in subchapters or parts, but in a continuous flow, presenting the context of the creation of the work and then immediately dedicating itself to listening to the work crossed by theoretical aspects that overlap and transpose, such as the height of the speaker’s voice in Isto. The article includes interviews given by Cildo Meireles to the author and, based on the artist’s interest in Topology, articulates investigations into high dimensions with the notion of loop. It thus proposes the sonorous as a possibility of a perceptual dimension in the arts in which listening takes place in the body as a whole through poetry.